Effects on numerical calculations of in-flight particle trajectories and temperatures considering multiple particle size and shape. (November 2020) - Knoll, M.; Gerhardter, H.; Prieler, R.; Hochenauer, C.; Tomazic, P.; Schröttner, H.
Abstract: In this work the effects on numerical calculations of in-flight particle motion and heating within a semi-industrial scale shaft furnace are presented. Therefore, experiments and numerical calculations with a type of boiler slag powder were conducted. It consists of particles with various size and shape. The obtained results were used for validation purposes of the proposed numerical model. This model differs in two main modifications compared to the current state-of-the-art CFD models. First, the application of a numerically inexpensive combustion model with a detailed chemical reaction mechanism enabled a significant reduction of the computational demand. Furthermore, the used burner type in the furnace with its characteristics can be modeled with sufficient accuracy. Second, various particle sizes and shapes were considered within the numerical model by application of corresponding drag formulations and empirically determined drag model parameters. Latter were obtained using a particle classification method proposed in a previous study. With this approach influences due to particle drag, rotation, oscillation and surface friction of different particle sizes and shapes were considered. Nevertheless, particle trajectories and heat transfer between particles and the fluid can be modeled with a low computational effort. The obtained results were compared to a commonly used approach, considering only one particle shape factor and one particle injection. Resulting particle trajectories and temperatures reveal significant differences between the latter and the proposed approach. Finally, influences on the heating characteristics due to preheated combustion air were investigated. It was shown that particle trajectory and temperature calculations in the shaft furnace are mainly affected by considering various particle shapes. Furthermore, the numerical results were improved by applying empiric model parameters. Using preheated combustion air as oxidizer results in a higher amount of spheroidized particles.